Edukasi Gizi Seimbang Ibu Hamil Melalui Pemberian Menu Seimbang Di Desa Julu’Pamai Kecamatan Pallangga Kabupaten Gowa - Buhari, Suharti; Haruna, Dian Maharani (STIKES Yayasan RS.Dr.Soetomo, 2025)
Fulfilling the nutritional needs of pregnant women is paramount during pregnancy. By obtaining balanced and good nutrition, pregnant women can reduce health risks to the fetus, one of which is an effort to prevent stunting in infants and toddlers. The problem of inadequate intake among pregnant women in Julu'pamai Village, Pallangga District, Gowa Regency, requires an appropriate intervention to prevent nutritional problems in pregnant women and their toddlers. The purpose of this community service activity is to improve the knowledge and skills of pregnant women in providing and consuming a balanced diet. The methods used include counseling, education, and creating balanced menus for pregnant women. The number of pregnant women has reached the target (20 people). The results of the community service activity show that after being provided with education, there was a 100% increase in the knowledge of mothers. There was an average increase in knowledge score of 1.6 between before and after being provided with education. Based on the mothers' skills in preparing a balanced menu at home, it also shows that 100% of pregnant women have been able to practice it at home. However, not all pregnant women have adopted the practice of eating a balanced menu. Pregnant women still rarely consume sources of vegetable protein and fruit.